2014
DOI: 10.7717/peerj.512
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational conflicts may help explain parental absence effects on reproductive timing: a model of age at first birth in humans

Abstract: Background. Parental absences in childhood are often associated with accelerated reproductive maturity in humans. These results are counterintuitive for evolutionary social scientists because reductions in parental investment should be detrimental for offspring, but earlier reproduction is generally associated with higher fitness. In this paper we discuss a neglected hypothesis that early reproduction is often associated with parental absence because it decreases the average relatedness of a developing child t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…If these males contributed significant familial and economic help to the family, the childrearing assistance provided by older females may have been offset. 4 Additional possibilities include the potential for greater conflict or competition for resources in larger households, which has been shown to be relevant to childbearing in other contexts (e.g., Flinn 1989; Strassmann 2011, Moya and Sear 2014), and the potential role of duration of marriage and its relationship to stopping behavior. Although we have no precise measurement in the data, women with more co-resident females age 11 and older likely had longer marriages than women without co-resident older females.…”
Section: Poisson Analysismentioning
confidence: 99%
“…If these males contributed significant familial and economic help to the family, the childrearing assistance provided by older females may have been offset. 4 Additional possibilities include the potential for greater conflict or competition for resources in larger households, which has been shown to be relevant to childbearing in other contexts (e.g., Flinn 1989; Strassmann 2011, Moya and Sear 2014), and the potential role of duration of marriage and its relationship to stopping behavior. Although we have no precise measurement in the data, women with more co-resident females age 11 and older likely had longer marriages than women without co-resident older females.…”
Section: Poisson Analysismentioning
confidence: 99%
“…For instance, a woman of reproductive age may provide help to her kin, acting as helper-at-the-nest (Kramer 2005); resulting in close kin more effectively reproducing, but the woman herself suffering a reduction in fertility. This may occur because of reproductive competition between generations (Cant and Johnstone 2008;Moya and Sear 2014).…”
Section: Hypothesized Causal Pathway Of Kin Influencementioning
confidence: 99%
“…In contrast, evidence from the matrilineal Khasi of northeast India has shown that kin, particularly mothers, may contribute to good marital choices and therefore reduce the likelihood of divorce (Leonetti et al 2007). Kin availability has been shown to have effects on many aspects of reproductive success including child survivorship (Borgerhoff Mulder 2007;Sear and Mace 2008;Sear et al 2002), age at marriage (Moya et al n.d.;Moya and Sear 2014), and reproductive rates (Sear and Coall 2011;Snopkowski and Sear 2013) and likely plays a role in marital dissolution as well.…”
Section: Predictions For Divorce and Remarriagementioning
confidence: 99%